Molecularly Imprinted Polymers-Coated CdTe Quantum Dots for Highly Sensitive and Selective Fluorescent Determination of Ferulic Acid. (8th July 2019) - Wang, Zhihong; Long, Ruiqing; Peng, Mijun; Li, Te; Shi, Shuyun
Abstract : Ferulic acid (FA), an important phenolic acid, is widely distributed in higher plants and presents many pharmacological effects. Therefore, sensitive determination of FA in complex matrix is necessary. Molecularly imprinted polymers-coated CdTe quantum dots (CdTe-QDs@MIPs) exhibited incomparable advantages because of their combination of excellent selectivity of MIPs and high sensitivity of QDs. Here, a fluorescent probe based on CdTe-QDs@MIPs was successfully fabricated for selective and sensitive determination of FA. MIPs shell was obtained by the reverse microemulsion method using FA, 3-(aminopropyl) triethoxysilane (APTES), and tetraethyl orthosilicate (TEOS), as template, functional monomer, and crosslinker. In optimal conditions, the fluorescence CdTe-QDs@MIPs sensor exhibited fast response (within only 3 min), high sensitivity (limit of detection, LOD at 0.85 μ g/l), excellent linear ranges (2–100 μ g/l) with a correlation coefficient of 0.9996, and distinguished selectivity for FA. Satisfactory recoveries from 91.8% to 110.3% were achieved with precisions below 6.6% for FA analysis in real pineapple juice and apple juice by developed CdTe-QDs@MIPs. The fluorescence results coincided well with those obtained by high-performance liquid chromatography (HPLC). It could be concluded that the resultant CdTe-QDs@MIPs offered a new way for rapid and sensitive analysis of FA in the complex matrix.